Mechanosensing, from forces to structures - Zhao, Feng; Long, Yuchen (Frontiers in Plant Science, 2022)
Sessile plants evolve diverse structures in response to complex environmental cues. These factors, in essence, involve mechanical stimuli, which must be sensed and coordinated properly by the plants to ensure effective growth and development. While we have accumulated substantial knowledge on plant mechanobiology, how plants translate mechanical information into three-dimensional structures is still an open question. In this review, we summarize our current understanding of plant mechanosensing at different levels, particularly using Arabidopsis as a model plant system. We also attempt to abstract the mechanosensing process and link the gaps from mechanical cues to the generation of complex plant structures. Here we review the recent advancements on mechanical response and transduction in plant morphogenesis, and we also raise several questions that interest us in different sections.